Digital alphabet - a challenge for the modern student and teacher - Jeličić, Ruža (Array, 2021)
The fruits of the digital age have become a key part of everyday life in hundreds of millions of households, offices and schools around the world. Our communication takes place far more via text messages and e-mail than face-to-face, and the first place we look for information is Google. The consequences of this technological ubiquity and electronic flood are significant shifts in the attitudes as well as in the behavior of students and teachers, and the goal of this paper is to examine these shifts. How is the digital age changing the opportunities, values and lives of students and teachers - what is happening now, what awaits us in the future? Can digital achievement really change the way students and teachers think or behave? Do both students and teachers learn a new alphabet - the digital alphabet?